Policy of decentralization and changing governance of higher education in Post-Mao China - Ka-Ho Mok (2002)
Unlike the Mao era when educational development was entirely directed by the central government, there has been a strong trend to diversification and decentralization of education in the post-Mao period. This article, being set in this context, examines how the policy of decentralization has affected the governance modes of higher education in Mainland China. More specifically, the article focuses on three major aspects of education governance, namely, financing, provision and regulation in education, with special attention given to examining the changing relations between the state, local governments and other agents in education delivery. One very significant consequence of the change is that the public-good functions of education, of which the state has taken the primary role of a reliable guarantor, have diminished. Nonetheless, the state's role as a regulator and overall service coordinator has been strengthened rather than weakened under the policy of decentralization. These recent developments in China's higher education also reflect the global trend of decentralization in educational governance. - Reproduced.
Keywords: Education - China; Decentralization - China; Higher education - China; Higher education